2020
DOI: 10.1021/acsomega.0c01179
|View full text |Cite
|
Sign up to set email alerts
|

Development of Deformable Calcium Carbonate for High Filler Paper

Abstract: Controlling the size and rigidity of calcium carbonate became possible. HCCs were developed and manufactured by the in situ reaction of carbon dioxide and calcium oxide, which were already preflocculated together with GCC using ionic polymers before the reaction. HCC is deformable under pressure during the papermaking process, and its degree of rigidity can be controlled by adjusting the fraction of calcium oxide. The size of HCC can be further controlled by adjusting shearing force. The more the fraction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Figure 4(a) shows the bulk of papers containing different fillers and how much the paper bulk was affected by the high wet pressing pressure. As presented previously in the literature (Jung and Seo 2015a;Jung and Seo 2015b;Kang et al 2020), the HCC-containing paper always gave remarkably higher bulk than the others, and the one pressed with two-fold higher wet pressing pressure, HCC-H, kept the bulk equivalent to GCC. The stiffness of the papers containing HCC that were pressed with high wet pressing pressure were still higher than those containing GCC and the pGCC in Fig.…”
Section: Mechanical Propertiessupporting
confidence: 75%
See 4 more Smart Citations
“…Figure 4(a) shows the bulk of papers containing different fillers and how much the paper bulk was affected by the high wet pressing pressure. As presented previously in the literature (Jung and Seo 2015a;Jung and Seo 2015b;Kang et al 2020), the HCC-containing paper always gave remarkably higher bulk than the others, and the one pressed with two-fold higher wet pressing pressure, HCC-H, kept the bulk equivalent to GCC. The stiffness of the papers containing HCC that were pressed with high wet pressing pressure were still higher than those containing GCC and the pGCC in Fig.…”
Section: Mechanical Propertiessupporting
confidence: 75%
“…It is known that the HCC-containing paper has much higher bulk than the GCCcontaining paper, while keeping high tensile strength and high stiffness from the previous study (Jung and Seo 2015a;Jung and Seo 2015b;Choi and Seo 2016;Choi et al 2018;Kang et al 2020). In the previous study, the authors demonstrated that the HCC containing paper could be used for developing highly filled paper without compromising essential mechanical properties (Kang et al 2020). This time, the authors tried to make use of the high bulk of HCC containing paper for developing the high solid content paper.…”
Section: Wet Pressingmentioning
confidence: 85%
See 3 more Smart Citations